Routledge Handbook of Global Sport (Florence)
1 online resource (535 p.).
Keywords: The story of global sport is the story of expansion from local development to globalized industry, from recreational to marketized activity. Alongside that, each sport has its own distinctive history, sub-cultures, practices and structures. This ambitious new volume offers state-of-the-art overviews of the development of every major sport or classification of sport, examining their history, socio-cultural significance, political economy and international reach, and suggesting directions for future research. Expert authors from around the world provide varied perspectives on the globalization of sport, highlighting diverse and often underrepresented voices. By putting sport itself in the foreground, this book represents the perfect companion to any social scientific course in sport studies, and the perfect jumping-off point for further study or research. The Routledge Handbook of Global Sport is an essential reference for students and scholars of sport history, sport and society, the sociology of sport, sport development, sport and globalization, sports geography, international sports organizations, sports cultures, the governance of sport, sport studies, sport coaching or sport management.